Validation of the Spanish version of the Adjustment Disorder New Module-20 (ADNM-20) in a non-clinical sample - Soledad Quero; Sara Fernández-Buendía; Jesús Privado; Jorge Grimaldos; Pim Cuijpers (BMC Psychology)
Abstract Background There is a lack of self-report measures specifically designed for Adjustment disorder. One of the most widely used instruments is the Adjustment Disorder New Module (ADNM), which has already been validated in different countries. The aim of this study was to validate the Spanish version of the ADNM-20 with a non-clinical sample, including a comparison with a high-risk sample. Method 203 participants of the general population (mean age = 33.84) completed an online survey which included the Spanish version of the ADNM, the anxiety and depression measures GAD-7 and PHQ-9, and an assesment of coping strategies using the Brief-COPE. Results The analysis of the scale’s internal structure revealed that a hierarchical model could best fit the data, as well as a bifactorial structure. The scale showed high internal consistency and an adequate differential validity, as differences were observed when comparing the high-risk and non-clinical groups. Positive correlations were also identified between ADNM and depression and anxiety, as well as different correlations with coping strategies. Conclusion This study presents the first validation of the ADNM-20 in Spanish showing good reliability and validity results. In addition, a comparison with a high-risk sample and norms are offered to help future evaluators.